Abductor digiti minimi opponensplasty for a patient with Cavanagh’s syndrome: A case report - Ali Parsa; Farzad Omidi Kashani; Mohammad Moghaddam; Abdolreza Malek; Ali Birjandinejad (Reviews in Clinical Medicine, 2018)
Thumb hypoplasia only in the intrinsic thenar muscles is a rare condition; this defect might be accompanied with cardiac diseases (Holt-Oram syndrome), ocular anomalies, and vascular anomalies of the hand and wrist (Okihiro syndrome). In addition, this condition may be detected in hypereosinophilic syndrome (HES), which gives rise to other hand anomalies, as well. Unilateral or bilateral absence of isolated thenar muscles is another rare abnormality.In this study, we presented a case of Cavanagh’s syndrome in an eight-year-old boy with right-sided thenar hypoplasia who had difficulty in thumb opposition. For the treatment, the patient underwent abductor digiti minimi (ADM) opponensplasty. After three years of follow-up, he regained thumb opposition and was symptom-free. Care must be taken to avoid misdiagnosis of thenar atrophy/hypoplasia with carpal tunnel syndrome in case of children.